2019
DOI: 10.4028/www.scientific.net/msf.970.145
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Welding Parameters for Small-Scale Resistance Spot Welding of Zirconium Alloys

Abstract: This paper presents the results of optimization of parameters for resistance spot welding of parts made of E110 zirconium alloy with a thickness of 0.25 + 0.25 mm. Its purpose was to determine the influence of welding current profiles on nugget metal structure and mechanical properties of welds. The highest tensile strength comparable with base metal (380...440 MPa) was observed when the ratio of integral heat input to current pulse duration was about two. Formation of martensitic structure and coarsening of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Immediately before welding, the parts had been degreased with C 2 H 5 OH ethyl alcohol. A special welding facility [12][13][14][15][16][17] was used that included an 'IPTKM-10' power source and a modernized 'MTT-02' welding gun. The 'IPTKM-10' power source was a digital synthesizer of unipolar current pulses with required algorithms regardless of the load resistance.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Immediately before welding, the parts had been degreased with C 2 H 5 OH ethyl alcohol. A special welding facility [12][13][14][15][16][17] was used that included an 'IPTKM-10' power source and a modernized 'MTT-02' welding gun. The 'IPTKM-10' power source was a digital synthesizer of unipolar current pulses with required algorithms regardless of the load resistance.…”
Section: Methodsmentioning
confidence: 99%
“…After analyzing the data presented in Table 1 and welding several trial joints, the current and pulse duration ranges were set from 3.3 to 5.1 kA and from 4 to 16 ms, respectively. Based on the recommendations of early SSRSW studies [3,4] and the authors' own experience [12][13][14][15][16][17], the preheating stage, as shown for modes 2 and 3 in Fig. 2, was also implemented to stabilize heat generation in accordance with Eq.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations